2007
DOI: 10.1534/genetics.106.069005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Triple Testcross Design With Recombinant Inbred Lines Reveals a Significant Role of Epistasis in Heterosis for Biomass-Related Traits in Arabidopsis

Abstract: Primary causes of heterosis are still unknown. Our goal was to investigate the extent and underlying genetic causes of heterosis for five biomass-related traits in Arabidopsis thaliana. We (i) investigated the relative contribution of dominance and epistatic effects to heterosis in the hybrid C24 3 Col-0 by generation means analysis and estimates of variance components based on a triple testcross (TTC) design with recombinant inbred lines (RILs), (ii) estimated the average degree of dominance, and (iii) examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
59
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 30 publications
16
59
1
5
Order By: Relevance
“…On the other hand, Yu et al (1997), applying twoway analyses of variance using all possible pairwise combinations of marker genotypes to test epistasis, and Luo et al (2001) and Li et al (2001), using a mixed linear model with background variation control to map simultaneously main and epistatic effects, reported that epistasis is a common feature of most loci associated with inbreeding depression and heterosis in rice. In Arabidopsis Kusterer et al (2007a) found a significant role of epistasis in the expression of heterosis while analyzing generation means and variance components for biomass-related traits in a triple-testcross design with a recombinant inbred line population. Furthermore, in a study on QTL mapping in Arabidopsis using NIL libraries Melchinger et al (2007b) found about three times more loci with significant additive 3 additive epistatic interactions with the genetic background than with dominance effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yu et al (1997), applying twoway analyses of variance using all possible pairwise combinations of marker genotypes to test epistasis, and Luo et al (2001) and Li et al (2001), using a mixed linear model with background variation control to map simultaneously main and epistatic effects, reported that epistasis is a common feature of most loci associated with inbreeding depression and heterosis in rice. In Arabidopsis Kusterer et al (2007a) found a significant role of epistasis in the expression of heterosis while analyzing generation means and variance components for biomass-related traits in a triple-testcross design with a recombinant inbred line population. Furthermore, in a study on QTL mapping in Arabidopsis using NIL libraries Melchinger et al (2007b) found about three times more loci with significant additive 3 additive epistatic interactions with the genetic background than with dominance effects.…”
Section: Discussionmentioning
confidence: 99%
“…S15), with the caveat that any correlation based on a large number of small-effect loci may be obscured by the moderate-effect size loci that we detected in the GWA studies. Several previous studies of heterosis using controlled crosses in A. thaliana have identified loci that exhibit all possible modes of gene action, including additive, dominant, and epistatic interactions (26)(27)(28)(94)(95)(96). Lack of support for the major heterosis hypotheses comes also from studies in crop species, particularly in maize and rice.…”
Section: Arabidopsis Thaliana In the Context Of Traditional Heterosismentioning
confidence: 99%
“…Finally, the pseudooverdominance hypothesis also explains heterosis with the complementation of recessive alleles but proposes that when linked in repulsion, such alleles appear overdominant. Outside of these classical hypotheses, some cases of hybrid inferiority (19)(20)(21)(22) and hybrid superiority (23)(24)(25)(26)(27)(28)(29)(30) have been linked to epistatic interactions between parental alleles.…”
mentioning
confidence: 99%
“…Although there have been a large number of genetic analyses in plants with results favoring one hypothesis or another (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), genetic composition pertaining to heterotic performance of crop hybrids has not been fully characterized in an experimental population. There has been no assessment about the relative contributions of these genetic components to heterosis in a crop hybrid.…”
Section: Epistasis | Recombinant Inbred Intercrossmentioning
confidence: 99%